The effects of three selected food items on the weight, reproductive capacity, and protein content of the golden miracle snails (Pila leopordvillensis) - Florendo, Magdalena G. (Animo Repository, 1987)
A 90-day feeding experiment was done under laboratory condition to determine the effects of 3 selected food items on the growth, reproductive capacity, and protein content of the Golden Miracle Snail (Pila leopordvillensis). The 3 food items which were given at libitum are gabi, camote, malunggay, and a mixture of the 3 items. The weight and size of the Golden Miracle Snails were determined initially and subsequently on the 45th, 70th, and 90th day. The reproductive capacity was based on the number of eggs produced and deposited on the walls of the aquaria. The protein contents of 45-day old snails and 90-day old snails were determined using the Biuret method. A t-test was used to compare the protein content of the 45-day old snails and that of the 90-day old snails. There were no significant differences in the weight, size and reproductive capacity among the snails given the different treatments. However, those fed with gabi and malunggay leaves showed relatively high mean weight and size increment. The camote-fed snails exhibited the lowest mean weight gain. Snails fed with malunggay leaves and mixed diet produced more eggs. Regardless of food items given, 90-day old snails yielded significantly higher mean protein content than the 45-day old snails.